The Role of Knowledge Makers in Building the Capabilities of Ingenious Organizations (Czech Journal of Multidisciplinary Innovations, 2023)
Contemporary organizations are interested in their knowledge makers, as they are an important and essential component in building the organizations’ Ingenious capabilities and their contribution to relative stability. The study of this research came to reveal the role of knowledge makers in the extent to which they enhance the capabilities of the skilled organizations at the University of Maisan, based on two main hypotheses revolving around the dimensions of Implicit to the main variables, by applying it to senior administrative leaders using the measurement tool (questionnaire) and the programs (SMART PLS, SPSS) and using the descriptive analytical approach. The research reached important conclusions, including that there is a positive and direct correlation and a moral impact relationship between knowledge makers and Ingenious organizations. This is explained by the fact that interest in knowledge makers leads to an increase in enhancing the capabilities of Ingenious organizations through attention to intellectual capabilities, searching for and analyzing information, creativity, and innovation, and there were several recommendations. The most important of which is the need to enhance the awareness of the senior leadership at the University of Maisan of the importance of Ingenious organizations and their dimensions, including contextual prowess and immediate prowess, and to explore opportunities to enhance these capabilities and reach an Ingenious organization that focuses on what is new, organizes the organizational components in the university and relies on flexibility and speed in detecting and exploiting available opportunities